Ausonius : Moselle, Epigrams, and Other Poems - Warren, Deborah (Routledge Later Latin Poetry, 2017)
Ausonius- Front Cover -- Ausonius -- Title Page -- Copyright Page -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- I. Historical context -- the life of Ausonius -- the poet's output -- II. Historical, literary, and poetic contexts of the poems translated in this volume -- III. Textual history, reception, and Latinity -- IV. Principles of selection and translation [D. W.] -- Notes -- The Moselle -- Notes -- The Epigrams -- 1. Prosopopoeia to the collection of Epigrams -- 2. Exhortation to humility -- 3. To the adulteress Eumpina -- 4. To the physician Eunomus -- 5. To the man with an unpleasant voice -- 6. On Auxilius the grammarian -- 7. On Philomusus the grammarian -- 8. On Rufus, a rhetorician -- 9. To a statue of the same rhetor -- 10. On the same subject -- 11. On the same subject -- 12. On the same subject -- 13. On the same subject -- 14. From the Greek: on the man who found treasure when . . . -- 15. From the Greek (the beginning is half of the whole) -- 16. From the Greek (he gives twice who gives soon) -- 17. From the same place -- 18. On a man who fell down dancing the role of Capaneus -- 19. On a brew called "Dodra" -- 20. On the same subject -- 21. On the same subject -- 22. To my friend Marcus about the discord which he describes with girls -- 23. Sick with love -- 24. On the man who wanted to destroy a skull pitilessly -- 25. On the worth of his manuscript -- 26. On Augustus -- 27. On a wild beast slain by Caesar -- 28. To the source of the Danube (at the command of the Emperor Valentinian) -- 29. For a marble statue for Valentinian the Younger -- 30. Inscribed under a picture where a lion is killed by Gratian with one arrow -- 31. To the source of the Danube, at the command of the Emperor Valentinian -- 32. To a picture of Echo -- 33. For a statue of opportunity and regret -- 34. To a girl, Galla, already aging.